"MANY‐CITEDNESS": CITATIONS MEASURE MORE THAN JUST SCIENTIFIC QUALITY. (27th January 2021) - D'Ippoliti, Carlo
Abstract: Citation counts are increasingly used to create rankings of scholars or institutions: while social scientists are often skeptical of the resulting indexes, economists have mostly been supporters of this approach. Yet, citation metrics have raised two debates in the literature: empirical, regarding their technical use, and theoretical, regarding their meaning and, more generally, the meaning of "scientific quality." I review this literature highlighting the consequences for the use of citations for research assessment. As an application, I further study the network of citations of publications indexed in Web of Science, authored by all Italian academic economists between 2011 and 2015. I find that the probability of a citation between any two authors depends on similarity in their methods and topics but also, significantly, on various measures of social community and even of ideological proximity. The influence of social relations does not cancel out in the aggregate, as total citations to an individual depend on their network centrality. In the case of economics, citations cannot be interpreted as unbiased proxies of scientific quality.